Paradiplomasi Melalui Sister City Pemerintah Kota Denpasar dan Mossel Bay : Implementasi dan Pengalihan Kerja Sama - Nisa, Hasri Maghfiratin (Global and Policy Journal of International Relations, 2022)
The sister city cooperation between Denpasar City and Mossel Bay City cannot be separated from the important role of cooperation that was carried out first between Indonesia and South Africa. The Government of Denpasar and the government of Mossel Bay have several things in extraordinary which have made them linked, particularly in the fields of tourism and trade. After one year of the inauguration of para-diplomacy activities between the two cities, the COVID-19 pandemic has hit the entire world, causing all activities and fields to be paralyzed. Para-diplomacy activities that should be actively met must be postponed and must be altered online. This study aims to determine the implementation of sister city cooperation activities between Denpasar and Mossel Bay and the virtual waivered of paradiplomacy. The method used is descriptive qualitative with data collection through the official website of the Ministry of Foreign Affairs, official website of Denpasar City Government, official website of Mossel Bay City Government. Paradiplomacy activities do not just halt, yet in these 3 years, activities have continued through online meetings.Keywords : Paradiplomacy, Sister City, Government of Denpasar, Government of Mossel Bay, Online Meeting.DOI: https://doi.org/10.33005/jgp.v10i01.3569